Constitutive characterization of an 1800 MPa press hardening steel under hot stamping conditions. Issue 1 (June 2021) - Lu, S; DiCecco, S; Worswick, M; Chiriac, C; Luckey, G; Tjong, J; Boettger, J; Shi, C
Abstract: High temperature isothermal tensile tests were performed on an aluminized 1800 MPa press hardening steel with a Gleeble thermal-mechanical test system. A procedure was developed to enable the use of digital image correlation (DIC) analysis of the tensile specimens. Flow curves ranging from 500°C - 900°C with strain rates ranging from 0.01 s −1 – 1 s −1 were obtained. To validate this DIC procedure, flow curves for the more common PHS1500 (22MnB5) steel were also obtained in an identical manner and compared to results found in the existing literature. The resultant flow curves were then post-processed and fit to a thermal-viscoplastic constitutive equation for numerical simulation implementation. Finally, a finite element model of the tensile test was created to evaluate the accuracy of the constitutive results.